Pendampingan Pengelolaan dan Pelaporan Keuangan Pondok Pesantren Al-Firdaus - Endri Juniyanto; Eha Nugraha; Dini Dewindaru (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: Presentation of Islamic boarding school financial reports is not in accordance with the Islamic Boarding School Financial Guidelines mandated by Bank Indonesia (BI) and the Indonesian Association of Accountants. Method: The tools used in this community service activity included laptops, LCDs, and accounting software. Office Excel, financial forms, and forms. Results: Indicators of the success of this activity can be identified in two stages of evaluation: initial evaluation and evaluation of the results. An initial evaluation was conducted by presenting interim financial reports based on simulation data from January 2022. The aim is to ensure that the forms are filled correctly and that the transactions reported in these forms are properly recorded in the journal. The results were evaluated to determine and ensure that all data entered were presented correctly and in accordance with Islamic boarding school accounting guidelines. Limitations: The lack of knowledge and educational background of administrative staff from non-accounting causes obstacles. Contribution: The results of the activity show that there is an increase in the understanding of employees in the finance departments of schools and Islamic boarding schools. This was evidenced by the enthusiasm of the participants in the question-and-answer form and discussion. Workshop participants were willing to carry out follow-up activities in the form of financial management assistance for schools and Islamic boarding schools in the future.